The pitch of chromatin DNA is reflected in its nucleotide sequence. - Trifonov, E N (1980)
A correlation analysis of chromatin DNA nucleotide sequences reveals the clear tendency of some of the dinucleotides to be repeated along the sequences with periods of 3 and about 10.5 bases. This latter period, which is equal within experimental error to recent estimates of the pitch of the DNA double helix [Wang, J. (1979) Proc. Natl. Acad. Sci. USA 76, 200-203; Trifonov, E. & Bettecken, T. (1979) Biochemistry 18, 454-456] is interpreted as a reflection of the deformational anisotropy of the DNA molecule that facilitates its smooth folding in chromatin.